Effects of upper limb vibratory stimulation training on motor symptoms in Parkinson's disease: an observational study - Valentina Varalta; Anna Righetti; Elisa Evangelista; Alberto Vantini; Alessandro Martoni; Stefano Tamburin; Cristina Fonte; Ilaria Antonella Di Vico; Michele Tinazzi; Andreas Waldner; Alessandro Picelli; Mirko Filippetti; et al. (Medical Journals Sweden, 2024)
Objectives: Parkinson's disease is characterized by motor and non-motor symptoms. Tremor is one of the motor symptoms that can affect manual skills and have an impact on daily activities. The aim of the current study is to investigate the effect of upper limb training provided by a specific vibratory device (Armshake®, Move It GmbH - Bochum, Germany) on tremor and motor functionality in patients with Parkinson's disease. Furthermore, the training effect on global cognitive functioning is assessed. Design: An uncontrolled before-after clinical trial. Patients: Individuals with diagnosis of Parkinson's disease, motor upper limbs deficits, and absence of dementia. Methods: Participants underwent a 3-week programme (3 times a week) and was evaluated before, after, and at 1 month follow-up by motor (Fahn Tolosa Marin Tremor Rating Scale, Unified Parkinson's Disease Rating Scale - part III, Purdue Pegboard Test, Disability of the Arm, Shoulder and Hand Questionnaire) and cognitive (Montreal Cognitive Assessment) scales. Results: Twenty subjects are included. After treatment a statistically significant improvement in tremor, manual dexterity and activities of daily living was found. The data indicated no effects on global cognitive functioning. Conclusion: These findings suggest positive effects of vibratory stimulation training on upper limb motor symptoms in Parkinson's disease.